In people with poorly controlled hypertension, self-management including telemonitoring is more effective than usual care for reducing systolic blood pressure at 6 and 12 months. Issue 1 (25th November 2010) - Earle, Kenneth
Abstract : Commentary on: McManus RJ Mant J Bray EP . Telemonitoring and self-management in the control of hypertension (TASMINH2): a randomised controlled trial . Lancet 2010 ;376 :163 –72 .